2018
DOI: 10.1097/jom.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Total Health-Related Costs Due to Absenteeism, Presenteeism, and Medical and Pharmaceutical Expenses in Japanese Employers

Abstract: Objective:This study aimed to examine a detailed breakdown of costs (absenteeism, presenteeism, and medical/pharmaceutical expenses), of the employees in four pharmaceutical companies in Japan.Methods:This is a cross-sectional study. Absenteeism and presenteeism were measured by a self-administered questionnaire for workers, and their costs were estimated using the human capital approach. Presenteeism was evaluated by the degree affected quality and quantity of work. Medical and pharmaceutical expenses were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
166
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 155 publications
(175 citation statements)
references
References 23 publications
3
166
0
6
Order By: Relevance
“…It has recently acquired social attention because the socio‐economic burden of presenteeism was estimated to cost 1.9–5.1 times more than the direct cost, including medical and pharmaceutical costs (Sainsbury Centre for Mental Health, ). According to a previous study conducted in Japan, the cost due to absenteeism was $520 per person per year and that due to presenteeism was $3,055 (Nagata et al, ). Moreover, presenteeism is a risk factor for future absenteeism and a decrement in self‐rated health (Bergstrom et al, ; Janssens, Clays, De Clercq, De Bacquer, & Braeckman, ; Taloyan et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently acquired social attention because the socio‐economic burden of presenteeism was estimated to cost 1.9–5.1 times more than the direct cost, including medical and pharmaceutical costs (Sainsbury Centre for Mental Health, ). According to a previous study conducted in Japan, the cost due to absenteeism was $520 per person per year and that due to presenteeism was $3,055 (Nagata et al, ). Moreover, presenteeism is a risk factor for future absenteeism and a decrement in self‐rated health (Bergstrom et al, ; Janssens, Clays, De Clercq, De Bacquer, & Braeckman, ; Taloyan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…$3,055 (Nagata et al, 2018). Moreover, presenteeism is a risk factor for future absenteeism and a decrement in self-rated health (Bergstrom et al, 2009;Janssens, Clays, De Clercq, De Bacquer, & Braeckman, 2013;Taloyan et al, 2012).…”
mentioning
confidence: 99%
“…Second, we tested the correlations between the WHO-HPQ measures and five possible predictors (two health conditions and three psychosocial job conditions. We assumed that WHO-HPQ absenteeism measures would correlate positively with psychological distress and depression/anxiety disorder 10) and negatively with job control, and supervisor and coworker support 26) ; Similarly, the WHO-HPQ presenteeism measures, for which the greater score implies better work performance 6) , would correlate negatively with psychological distress and depression/anxiety disorder, and positively with job control, and supervisor and coworker support 27) .…”
mentioning
confidence: 99%
“…It is interesting to note that while OPs in other studies in Japan, like the OPs in the present survey, reported spending many hours for health examination and follow-up 24) , or health counseling 22) , OPs in other studies reported spending less time on management of mental health issues and over-work cases than OPs in the present analysis. Management of mental health and health hazards due to overwork, however, has been among the important / 21 issues of OH 3,25,26) . The report of Japan Medical Association 22) In 2016, majority of OP felt difficulty in SC-related issues, especially in interview with high-stress employees ( Table 5).…”
Section: The Results Of Classification By Type Of Business Of Enterprmentioning
confidence: 99%